PUBLIC EXPENDITURE MANAGEMENT IN INDONESIA: - Jaelani, Aan (State Institute of Islamic Studies (IAIN) Palu, 2018)
This paper discusses the management of public expenditures in Indonesia in State Budget 2017. The data collected from fiscal policy documents, especially about government spending plans in 2017, and then be reviewed by policy analysis, the theory of public expenditures, and the theory of public goods, and compared with the theory of public expenditure in Islamic economics. Public expenditure management in Indonesia has implemented a distribution system that divided public expenditure for central government expenditures, transfers to the regions, and the village fund. In terms of fiscal policy, public expenditure priorities to support the achievement of sustainable economic growth, job creation, poverty reduction, and the reduction of gaps in the welfare of the whole community. In Islamic economics, public expenditure is used to meet the needs of the community based on the principles of general interest derived from the sharia. Public expenditure on Indonesia’s government as an effective tool to divert economic resources and increase the income of society as a whole, and focused on the embodiment of the people’s welfare.